Leader Machiavellianism and follower silence - Hakan Erkutlu; Jamel Chafra (European Journal of Management and Business Economics (EJM&BE), 2019)
Purpose Drawing on the social exchange theory, the purpose of this paper is to examine the relationship between leader Machiavellianism and employee's quiescent silence. Specifically, the authors take a relational approach by introducing employee's relational identification as the mediator. The moderating role of psychological distance in the relationship between leader Machiavellianism and quiescent silence is also considered. Design/methodology/approach Data were collected from nine universities in Turkey. The sample included 793 randomly chosen faculty members along with their department chairs. Hierarchical multiple regression analysis was conducted to test the proposed model. Findings The results of this study supported the positive effect of leader Machiavellianism on employee's quiescent silence as well as the mediating effect of employee's relational identification. Moreover, when the level of psychological distance is low, the relationship between leader Machiavellianism and quiescent silence is strong, whereas the effect is weak when the level of psychological distance is high. Practical implications The findings of this study suggest that educational administrators in the higher education should be sensitive in treating their subordinates, as it will lead to positive interpersonal relationship, which, in turn, will reduce workplace silence. Moreover, they should pay more attention to the buffering role of psychological distance for those subordinates with high distrust and showing silence. Originality/value This study contributes to the literature on organizational silence by revealing the relational mechanism between leader Machiavellianism and employee quiescent silence. The paper also offers a practical assistance to employees in the higher education and their leaders interested in building trust, increasing leader-employee relationship and reducing workplace silence.
Keywords: 650; Psychological distance; Relational identification; Leader Machiavellianism; Quiescent silence